Republic of Estonia : Staff Report for the 2014 Article IV Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2014)
This 2014 Article IV Consultation highlights that in 2013, Estonia's recovery from the crisis continued but at a slower pace. Real GDP growth was 0.8 percent, with private consumption providing the main support, although net exports made a negative contribution. Inflation declined to about 3 1\2 percent, but stayed above the euro average. Public finances remained strong, with a fiscal deficit of 0.2 percent of GDP and a gross public debt of 10 percent of GDP. Real GDP growth is projected at 2.4 percent in 2014, rising toward expected potential growth of 3 to 3.5 percent in the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet